Dismal outcomes of patients with relapsed/refractory Philadelphia chromosome‐negative B‐cell acute lymphoblastic leukemia after failure of both inotuzumab ozogamicin and blinatumomab. Issue 6 (17th March 2022) - Short, Nicholas J.; Macaron, Walid; Konopleva, Marina; Ravandi, Farhad; Jain, Nitin; Issa, Ghayas C.; Kadia, Tapan; Sasaki, Koji; Kebriaei, Partow; Yilmaz, Musa; Thompson, Philip A.; Takahashi, Koichi; et al.
Abstract :